A Comparison of Methamphetamine-Induced Psychosis and Schizophrenia: A Review of Positive, Negative, and Cognitive Symptomatology - Wearne, Travis A.; Cornish, Jennifer L. (Frontiers in Psychiatry, 2018)
Methamphetamine is a potent psychostimulant that can induce psychosis among recreational and chronic users, with some users developing a persistent psychotic syndrome that shows similarities to schizophrenia. This review provides a comprehensive critique of research that has directly compared schizophrenia with acute and chronic METH psychosis, with particular focus on psychiatric and neurocognitive symptomatology. We conclude that while there is considerable overlap in the behavioral and cognitive symptoms between METH psychosis and schizophrenia, there appears to be some evidence that suggests there are divergent aspects to each condition, particularly with acute METH psychosis. Schizophrenia appears to be associated with pronounced thought disorder, negative symptoms more generally and cognitive deficits mediated by the parietal cortex, such as difficulties with selective visual attention, while visual and tactile hallucinations appear to be more prevalent in acute METH-induced psychosis. As such, acute METH psychosis may represent a distinct psychotic disorder to schizophrenia and could be clinically distinguished from a primary psychotic disorder based on the aforementioned behavioral and cognitive sequelae. Preliminary evidence, on the other hand, suggests that chronic METH psychosis may be clinical similar to that of primary psychotic disorders, particularly with respect to positive and cognitive symptomatology, although negative symptoms appear to be more pronounced in schizophrenia. Limitations of the literature and avenues for future research are also discussed.